The Constitution and Interpretation of the Authority Dilemma for the Leadership of the National Defence After Estonia Regained its Independence - Lill, Hellar (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2014)
After the restoration of independence in August 1991, Estonia had no national defence, defence capability or capacity for international defence cooperation. The armed forced had to be ‘invented’. However, this can be regarded as an advantage, since retraining and reorganising an existing system is usually more difficult. The main principles of national defence were established in Chapter 10 of the Constitution, which was approved in a referendum held in June 1992. This chapter, which was influenced by the presidential constitution of 1937/1938, did not answer the question of whether the Commander of the Defence Forces would be placed under the authority of the President, the parliament or the government. Two voluntary national defence organisations, the Defence League and the Home Guard, which competed with each other, already existed in Estonia when the Defence Forces were established. The Ministry of Defence was established even later. There were fears that subordinating the Commander of the Defence Forces to the government may lead to the politicisation of the army and uneven development due to frequent changes of government. These problems were eased by subordinating the commander to the President – however, this caused tension between the Ministry of Defence and the Defence Forces Headquarters. The parliament had the right to appoint and remove the Commander of the Defence Forces, but the proposal had to come from the President. This conflict culminated in summer 2000 when the Commander of the Defence Forces was removed as a result of a vote in the Riigikogu, which the President called an issue of civilian control; the removal, as well as the Defence Minister and government keeping their positions, was decided by one vote, allegedly given by accident…  The Constitution was amended in 2011. The President remains the highest leader of national defence, but executive power in the leadership of national defence has been granted to the government.